PENGARUH PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN BIBIT TANAMAN JATI PUTIH (Gmelina arborea Roxb) - Josina Irene Brigetha Hutubessy (Agriculture Faculty of Flores University, 2013)
This research aims to determine the effect of concentration of organic fertilizer Super NASA to the growth of seeds of white teak and to know the optimum dosage of organic fertilizer Super NASA can increase the growth of NASA plant seed white teak. The design used in this study was a Randomized Block Design with the treatment used is N0: without fertilizer Super NASA NASA, N1: Fertilizer NASA7 .5 ml seeds-1, N2: Fertilizer NASA 15 ml seeds-1, N3: Fertilizer NASA 22.5 ml seeds-1, N4: Fertilizer NASA 30 ml seeds-1. Variable observation in this study is the height of the plant, number of leaves, leaf area, fresh weight tan-1, fresh and dry weight oven tan-1. The results showed that the granting of Fertilizer NASA exerted a highly significant effect on the height of plant (23,65%), the number of leaves is not significant, leaf area (53,61%), fresh weight tan-1 (60,89%) and dry weight tan-1 (55,43%). The optimum dosage of Fertilizers NASA give the seed growth of white teak is best on the seed-1is 30 ml.